Cetuximab in the treatment of advanced non-small cell lung cancer: FISHing for a miraculous catch - Landi, Lorenza; Rossi, Antonio (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Non-small cell lung cancer (NSCLC) is divided in two main histologies: non-squamous and squamous histotypes. In metastatic non-squamous NSCLC patients, the oncogene-addicted subgroups are characterized by the presence of epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK) and proto-oncogene tyrosine-protein kinase 1 (ROS1) deregulations which can benefit, in the current practice, by specific tyrosine kinase inhibitors (TKIs).